The Effects of Lighting Intensity on the Productivity of Textile Workers in Surakarta (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
The textile industriesâ€™ growth in 2018 have contributed to national economic growth (Kemenperin, 2018). Enhancing competitiveness through conductive business climate is a strategic step to increase productivity (Kemenperin, 2017).Â Surakarta is one of the major cities in Indonesia famous for its textile products. Based on Indonesian Statistic Center, in 2016, the national textile industry productivity declined to 7.65%, directly affecting the productivity of textile industries in Surakarta, including PT IT. The weaving department of PT IT experienced the highest decline in work productivity with physical factor exposure more than Threshold Limit Value (TLV), including lighting intensity. This research aimed to analyze the correlation between the light intensity and worker productivity in 2018. This was a quantitative observational analytic research with cross sectional design in PT IT. From 50 workers in the weaving department, 32 were selected as samples through random sampling method. Light intensity was measured using Lux Meter ANA 999 in 32 measurement points. Work productivity was calculated using Productivity formula= Output (O)/ Input (I). Spearman correlation and SPSS program were used for data analysis. The result showed that there was a significant correlation between light intensity and workerâ€™s productivity (p=0.000, r=0.629).